The role of uric acid in the risk of hypertension developed from prehypertension: a five-year Chinese urban cohort study - Jun Zhu; Lingyu Shen; Shifen Jia; Wei Wang; Yaqing Xiong (BMC, 2024)
Abstract Background Uric acid as a prominent causal factor in the pathogenesis of hypertension is well recognized. Nevertheless, the influence of uric acid on the transition from prehypertension to hypertension within the Chinese population remains understudied. Methods A cohort of 1,516 prehypertensive individuals, aged 35 to 84 years, underwent recruitment following a comprehensive health assessment in 2017 and subsequent re-evaluation in 2022. Baseline characteristics and relevant clinical data were collected. The analytical approach encompassed multiple logistic regression and propensity score matching. Results Over 5 years, the cumulative incidence of hypertension amounted to 35.1%, with 33.9% in males and 37.3% in females, respectively. Notably, prehypertensive subjects concomitant with hyperuricemia exhibited a higher cumulative incidence of hypertension in comparison to the non-hyperuricemic counterparts (40.7% vs. 34.0%, p = 0.041). Multiple logistic regression unveiled a significant association between hyperuricemia and heightened hypertension risk (adjusted odds ratio [OR] = 1.44; 95% confidence interval [CI], 1.05-1.98; p = 0.022). Nonetheless, this association did not reach statistical significance when examining female subjects (adjusted OR = 1.10; 95% CI, 0.58-2.09; p = 0.781) or participants aged ≥ 60 years (adjusted OR = 1.07; 95% CI, 0.61-1.88; p = 0.814). Further validation through propensity score matching affirmed that subjects afflicted by hyperuricemia experienced a substantially elevated risk of transitioning from prehypertension to hypertension over the course of five years compared with the non-hyperuricemic counterparts (41.3% vs. 32.3%, p = 0.045), after adjusting for 12 covariates including age and gender. Hyperuricemia emerged as an independent risk factor predisposing individuals to the development of hypertension from a prehypertensive state. Conclusion This observation prompted the formulation of a hypothesis suggesting that ameliorating elevated uric acid levels may potentially mitigate the progression from prehypertension to hypertension.